(untitled) (The Review of Diabetic Studies, 2025)
Background: Knee osteoarthritis is a prevalent degenerative joint disorder that leads to pain, stiffness, and functional disability. Quadriceps muscle weakness contributes significantly to disease progression and reduced mobility. Exercise therapy is an established conservative treatment, while kinesiotaping has recently gained attention as a complementary technique for pain relief and functional improvement. This study aimed to evaluate the combined effect of quadriceps strengthening exercises and kinesiotaping on pain, functional ability, and range of motion in individuals with knee osteoarthritis. Methods: A randomized controlled trial was conducted on 60 participants diagnosed with mild to moderate knee osteoarthritis. Participants were randomly assigned into three groups: Group A received quadriceps exercises combined with kinesiotaping, Group B performed quadriceps exercises only, and Group C served as a control group receiving lifestyle advice. Interventions lasted eight weeks, with outcome measures assessed at baseline and post-intervention, including pain intensity using the Visual Analogue Scale (VAS), functional ability using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and knee range of motion using a goniometer. Statistical analysis was performed using SPSS version 26, with significance set at p < 0.05. Results: Both Group A and Group B showed significant improvements in pain, function, and range of motion compared to the control group (p < 0.001). Group A demonstrated the greatest improvement, with a 56.8% reduction in pain, a 43.5% improvement in WOMAC scores, and a 17.5% increase in knee range of motion. Between-group comparisons revealed that combining kinesiotaping with exercises produced significantly better outcomes than exercises alone (p < 0.001). Conclusion: The combination of quadriceps strengthening exercises and kinesiotaping was more effective than exercise alone or no intervention in reducing pain, enhancing functional ability, and improving knee mobility in patients with knee osteoarthritis. These findings suggest that kinesiotaping can serve as a valuable adjunct to exercise therapy, offering a non-invasive, cost-effective, and efficient approach to the conservative management of knee osteoarthritis.